An exploration of the other and the disruption of self in schizophrenia - Stopforth, Penny (Rhodes University, Faculty of Humanities, Department of Psychology, 2014)
Hermans' (2002) Dialogical model of Self advocates for a construction of Self that is fluid, diverse and dialogically constructed. He argues that development of ongoing dialogues from within and without the Self constitute the Self. These parts of Self that participate in this internal dialogue are referred to by Hermans (2002) as I-positions. Healthy, dynamic internal dialogue between I-positions is argued to contribute to maintaining a unified sense of Self. The Self is also argued to be socially constructed, in so far as Others outside the Self participate in these internal dialogues and are able to influence and occupy I-positions. Research has shown that people with a diagnosis of Schizophrenia experience a unique form of Self disruption. It has been postulated that this disruption is due to disruptions in this internal dialogue. To date, seminal research has primarily focussed on the internal mechanisms and phenomenological accounts of these disruptions. However, little research has focused on the role that Others outside the Self play in these disruptions. Since the Self is also constructed as a social entity, the aim of this research is to explore in what ways the Other contributes and/or minimises this disruption in people with a diagnosis of Schizophrenia. In order to achieve this, I made use of archival data which was made up of the transcripts from semi-structured interviews previously conducted with people with a diagnosis of Schizophrenia as part of a Self and Schizophrenia study. The interviews were analysed using deductive thematic analysis, and utilised Herman's theory of the Dialogical Self as the theoretical lens for this study. The emergent themes were organised according to those that were present before a diagnosis of Schizophrenia was given and those themes that were present post-diagnosis. The themes reflected that the Other plays a significant role in the both the maintenance of healthy dialogue post diagnosis and well as in the disruption of dialogue. This disruption was primarily observed throughthecompromising of previous I-positions and in the development of new performative and deficit I-positions that contributed to the disruption in internal dialogue.
Keywords: Self; Schizophrenia